Jack the Ripper and black magic: Victorian conspiracy theories, secret societies and the supernatural mystique of the Whitechapel murders - Dimolianis, Spiro; Evans, Stewart P. (McFarland, 2011)
"Jack the Ripper is a legendary gothic tale of Victorian conspiracies, the supernatural, secret societies and the police. Scotland Yard hunted a serial killer shrouded in politics as the mutilator of East End prostitutes infused pop culture with horror. This book uses historic sources and rare official reports to reveal dark and supernatural aspects of the Ripper case"--Provided by publisher